2020
DOI: 10.1111/ncn3.12372
|View full text |Cite
|
Sign up to set email alerts
|

When does cerebral β‐amyloid deposition begin in Lewy body dementia?

Abstract: Lewy body dementia (LBD) consists of two dementia syndromes associated with Lewy body pathology: Parkinson's disease with dementia (PDD) 1 and dementia with Lewy bodies (DLB). 2 In both disorders, cortical Lewy bodies (LBs) and Lewy neurites are often widespread and correlate with the severity of the dementia. The common pathological basis in the central, peripheral, and autonomic nervous systems supports considerable clinical overlap between them. The typical cognitive profiles are prominent impairments of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 66 publications
(165 reference statements)
0
8
0
Order By: Relevance
“…In previous pathological studies, patients with DLB showed a higher burden or phase of amyloid pathology than those with PD. [4][5][6][7][8] Another in vivo 11 C-labeled Pittsburgh compound B ( 11 C-PiB)-PET study found increased amyloid load in patients with DLB, particularly in the frontal and cingulate cortices, whereas 11 C-PiB uptake was infrequent or less in those with PD. 1,9,10 Similarly, our amyloid PET imaging showed that the DLB group had a higher burden of amyloid accumulation than the PD group in all cortical areas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous pathological studies, patients with DLB showed a higher burden or phase of amyloid pathology than those with PD. [4][5][6][7][8] Another in vivo 11 C-labeled Pittsburgh compound B ( 11 C-PiB)-PET study found increased amyloid load in patients with DLB, particularly in the frontal and cingulate cortices, whereas 11 C-PiB uptake was infrequent or less in those with PD. 1,9,10 Similarly, our amyloid PET imaging showed that the DLB group had a higher burden of amyloid accumulation than the PD group in all cortical areas.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to Lewy body pathology, concomitant Alzheimer's disease (AD) pathology is commonly observed in LBD, and clinicopathological studies have shown that 30% to 40% of patients with PD and up to 70% of patients with DLB have comorbid amyloid pathology 1‐3 . Generally, the prevalence and severity of amyloid pathology are higher in patients with DLB than in patients with PD or PD dementia (PDD) 4‐8 . In vivo amyloid positron emission tomography (PET) studies have also shown that the burden of amyloid was higher in the DLB group than in the PD and PDD groups 9‐11 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…No clear definition of Lewy body disease as a clinical term Based on current clinical diagnostic criteria, LBD consists of DLB and Parkinson's disease (PD). 1,26,27 Longitudinal follow-up studies have revealed that most patients with isolated RBD developed DLB or PD, and, in rare cases, multiple system atrophy. Therefore, isolated RBD is proposed to be included as another clinical phenotype of LBD.…”
Section: Terminology Regarding Lewy Body Diseasementioning
confidence: 99%
“…Recent advances in understanding of the prodromal stages indicate a wider clinical spectrum of LBD according to prodromal diagnostic criteria. 14,[26][27][28][29] Considering the lack of a clear definition of LBD beyond a generic term, LBD is used as the pathological term to avoid confusion with the clinical term in this article.…”
Section: Terminology Regarding Lewy Body Diseasementioning
confidence: 99%